PEMBERIAN ASIMILASI BAGI NARAPIDANA SEBAGAI PENERAPAN UNDANG-UNDANG PEMASYARAKATAN PADA LEMBAGA PEMASYARAKATAN KELAS IIA PADANG - Yudiansyah, Mai (UNES Journal of Swara Justisia, 2018)
The guidance of prisoners conducted under the Correctional system aims to getinmates prepared according to reunite with the community, so as to te-act as to be afreeman and have responsibility as member of society. To make the purpose happen, one ofthe efforts that have been made is assimilation. Based on the introduction and to get thesolution, the author formulate some of the problems such as follows: 1. How is theimplementation of guidance of convicts in the stage of Assimilation in Class IIA StatePenitentiary of Padang that has been applied so far? 2. What are the problems inimplementing the assimilation of prisoners in the Class IIA Penitentiary of Padang andhow to overcome these obstacles? 3. How good is the prospect of implementing theassimilation as an effort to foster prisoners based on the Correctional Law? The methodused in the thesis is analytical descriptive with normative juridical approach. Alsosupported by an empirical juridical approach. The data source that author use issecondary data and primary data. The data obtained were analyzed qualitatively andpresented in analytical descriptive form. Based on the results of research and discussion, itcan be concluded that the Implementation of Prisoners Assimilation Stage in Class IIAState Penitentiary of Padang has been implemented in accordance with applicableprocedures, but actually the implementation of it, constraints and obstacles has been foundwhich experienced by warden and prisoner itself, the lack of socialization of officers toprisoners, Family visiting can not run well due to overcapacity, there is still unenthusiasticattitude from some inmates in following assimilation activities, guarantors that are not inaccordance with the rules, the absence of family as a guarantor, out of town guarantor, theJustice Collaborator (JC) processing difficulties, the lack of budget within theCorrectional Institution.